Analisis Variasi Type Blade Impeller Produk 3d Printing Dengan Filamen St-Pla Pada Waterjet Thruster Mini Terhadap Performa Daya Dorong Dengan Metode Taguchi - Hasdiansah, Hasdiansah; Stevanus Seva, Marcellino; Oktavianto, Mario; Ahadiatullah, Wassi; Muhammad Ahlan Maulidiansyah; Viniolita, Thala (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Bangka Belitung Islands Province which consists of two islands, namely Bangka Island and Belitung Island, with such a geographical position, transportation is needed to facilitate connecting the two islands. The innovation of 3D printing used in transportation is in the form of a Waterjet Thruster using ST PLA (Super Tough Polylactic Acid) filament as a material for making parts of the Waterjet Thruster in the form of Inlets, Impeller, and Turbo Outlets. The Taguchi method is used to randomize the levels and factors in this test so that later the right combination can be found. In the tests that have been carried out, the highest results were found in experiment 8 with variations of 13 blade inlets, impeller 3 blade Type 2 and 9 Blade Outlet with thrust of 2.226 Newton while for the lowest value in Experiment 7 with variations of 13 Blade Inlet, Impeller 3 Blade Type 1 and Outlet 13 Blade with thrust 1.245 Newton.